2023
DOI: 10.1111/jrh.12741
|View full text |Cite
|
Sign up to set email alerts
|

Transactional sex among rural, justice‐involved Appalachian women who use drugs

Abstract: PurposeTransactional sex is associated with an array of other health risk behaviors and adverse health outcomes, including HIV. However, despite concerns regarding a potential HIV outbreak, there is limited understanding of transactional sex among rural Appalachians who engage in high‐risk behaviors. Thus, the current study describes the prevalence and correlates of transactional sex among a sample of rural, justice‐involved Appalachian women who use drugs.MethodsParticipants (N = 400) were randomly selected, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…Similar to previous research, women who engaged in transactional sex were more likely to experience sociostructural risk factors such as violence (Dickson et al, 2023;Dunkle & Decker, 2013), homelessness (Jenness et al, 2011;Kaljee & Chen, 2011), and criminal justice involvement (Sherman et al, 2018). These results are consistent with previous literature that details how cyclical police contact and homelessness create barriers to employment and other income-generating ventures (Menza et al, 2020;Rosen et al, 2022).…”
Section: Sociostructural Risk Factors and Violence Against Women And ...supporting
confidence: 89%
See 2 more Smart Citations
“…Similar to previous research, women who engaged in transactional sex were more likely to experience sociostructural risk factors such as violence (Dickson et al, 2023;Dunkle & Decker, 2013), homelessness (Jenness et al, 2011;Kaljee & Chen, 2011), and criminal justice involvement (Sherman et al, 2018). These results are consistent with previous literature that details how cyclical police contact and homelessness create barriers to employment and other income-generating ventures (Menza et al, 2020;Rosen et al, 2022).…”
Section: Sociostructural Risk Factors and Violence Against Women And ...supporting
confidence: 89%
“…Gendered disempowerment coupled with financial need may compromise the women’s ability to negotiate for increased condom use and avoid unsafe sex practices. Similar to research on incarcerated White women (Dickson et al, 2023), women in the current study also had more economic motivations for engaging in transactional sex; therefore, it is possible that economic dependence on sexual partners contributes to the increased risk of HIV among Black women who report opioid misuse.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…53,54 For example, one study of incarcerated women in rural Appalachian, more than one-quarter reported having traded sex for drugs, money, or other services in the year before incarceration. 55 There is also evidence to support a correlation between arrest and/or incarceration and number of different sexual partners, occurrences of unprotected sex, and concurrent partners. 56 Among justice-involved women who use substances, risky sexual practices appear to be even more common.…”
Section: Health and Transmitted Infectionsmentioning
confidence: 99%